PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN LITERASI SAINS BERBASIS GENDER PADA MATERI SISTEM PENCERNAAN - Srikandi, Mei Maharani; Sujana, Atep; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2017)
Indonesian students have low science literacy skills. It is known from PISA results that Indonesian students’ average score is lower than international average score. The purpose of this study is to find out the influence of contextual teaching and learning on students’ science aspects. The method used is pre-experimental with one-group pretest-posttest design. The sample in this study is the fifth grade students of SDN Situraja in 2016/2017 academic year, which amounted to 63 students. The instrument used is science literacy test type description that refers to science literacy aspect. The results showed a significant increase in science literacy skills after applied contextual teaching and learning. But, there was no significant difference between male and female students. However, there are differences in basic intelligence and social factors between male and female students.